Analysis the Effect of Capital Structure and Board Size on Firm Value in Companies Listed in Index LQ 45 - B12111014, Yuni Aprayi (Jurnal Manajemen Update, 2015)
This study aimed at finding out the effect of capital structure and board size on firm value in companies listed in Index LQ 45 from 2010-2014. The sample were determined based on the purposive sampling method thus this study was conducted by involving 15 companies listed in Index LQ 45. The analysis was made by using panel data regression analysis and the data testing was conducted in support of Eviews 7, while the classical assumption test is performed by using SPSS 17. The results of random effect method shows that: (1) Capital structure has significant and negative effect on firm value, (2) Board size has significant and negative effect on firm value, and (3) Firm size, as the control variable, has significant and negative effect on firm value. In conclusion, the results of the study indicated that all independent variables and control variable is partially and simultaneously affecting firm value in listed companies in Index LQ 45 from 2010-2014. Keywords: Capital Structure, Board Size, Firm Value, Index LQ 45.